Why Indian firms issue stock distributions. Issue 7 (13th July 2015) - Baker, H. Kent; Kapoor, Sujata
Abstract : Purpose: – The purpose of this paper is to investigate the opinions of managers of Indian firms on stock splits and bonus shares (stock dividends) and relate them to explanations for stock distributions identified in the prior literature. Design/methodology/approach: – The authors use descriptive statistics from a mail survey to the company secretaries of 500 firms listed on the National Stock Exchange of India to elicit their responses about statements involving stock splits and bonus shares. Findings: – The survey evidence shows that among the competing motives for stock splits, the liquidity hypothesis receives the highest level of support followed by the attention-getting variant of the signaling hypothesis, signaling, and the preferred trading range hypotheses. Regarding bonus shares, respondents express strong support for the retained earnings, liquidity, and signaling hypotheses but lesser support for the cash substitution and preferred trading range hypotheses. Research limitations/implications: – The survey evidence provides new insights into the stated motivations for stock distributions, especially bonus shares, among Indian firms but the ability to generalize the results is tempered by the relatively small number of respondents. This limits the ability to test for statistically significant differences between the various competing hypotheses. Hence, the results are suggestive rather than definitive. Practical implications: – The survey evidence suggests that no single explanation dominates all others for issuing stock splits or bonus shares in India. Thus, managers have multiple reasons for engaging in stock distributions. Originality/value: – Few studies use survey methodology to examine Indian dividend policy. Given the dearth of survey evidence on stock distributions among Indian firms, this study not only updates the limited evidence on stock splits but also provides the first survey evidence about managerial views on bonus shares.